The effect of task-based learning on students’ English-speaking fluency - Rizky Yolanda; Weni Ratnasari; Muhammad Ari Saputra; Zelly Putriani (Early Publishing Group, 2025)
This study underscores the critical importance of developing speaking fluency in English language learners, as fluency is central to effective communication in real-world contexts. Despite extensive research on language proficiency, there remains a gap in systematically understanding how instructional approaches, specifically Task-Based Learning (TBL), influence measurable aspects of speaking fluency such as speech rate, pauses, and utterance length. Current pedagogical practices often conflate fluency with general speaking ability without isolating its distinct features, thereby limiting targeted instructional strategies. The primary aim of this research is to evaluate the effectiveness of TBL in enhancing English-speaking fluency among undergraduate students. Employing a quasi-experimental design, the study involved 63 participants enrolled in an English education program, divided into experimental and control groups. Data were collected through pre- and post-intervention oral tests, which included picture descriptions and role-play scenarios, recorded and analyzed for fluency indicators using established rubrics. Data analysis involved comparative statistical procedures to assess differences in fluency measures between groups and over time. Key findings demonstrate that students who engaged with TBL exhibited significant improvements in speech rate, utterance length, and reduced hesitation, indicating enhanced fluency. The results reinforce that TBL's emphasis on authentic, communicative tasks facilitates more spontaneous, fluid speech. Implications suggest that incorporating structured, task-based activities into language curricula can effectively promote measurable fluency gains and foster learner confidence and motivation. The study advocates for the integration of fluency-specific assessment tools in language teaching, and recommends future research to explore the long-term effects of TBL on oral proficiency, thereby contributing to more targeted and effective language instruction methodologies.